Extracellular vesicles in osteoarthritis: mechanisms, therapeutic potential, and diagnostic applications - Sun, Chongxiao; Teng, Fei; Xia, Yayi (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is a chronic joint disease characterized by cartilage degradation, inflammation, and bone structural changes, leading to significant disability. Current therapeutic strategies, including traditional treatments and stem cell-based therapies, face limitations such as inability to prevent disease progression, immunogenic rejection, and tumorigenic risks. Extracellular vesicle (EVs), nanoscale membrane-bound vesicles secreted by cells, has emerged as a promising cell-free therapeutic approach due to their low immunogenicity, stability, and ability to mediate intercellular communication. This review summarizes the roles of EVs derived from various cell types, including cartilage progenitor cells (CPCs), bone marrow mesenchymal stem cells (BMSCs), synovial mesenchymal stem cells (SMSCs), adipose-derived stem cells (ADSCs), and immune cells, in OA pathogenesis and treatment. EVs exhibit multifaceted therapeutic potential, including immunomodulation, chondrocyte regeneration, and anti-inflammatory effects. Additionally, EVs serve as diagnostic biomarkers, offering non-invasive early detection of OA. Despite their promise, challenges such as scalability, targeting efficiency, and safety concerns remain. This review highlights the potential of EVs as both therapeutic agents and diagnostic tools, paving the way for innovative OA management strategies.